Biodiversitas Perikanan Di Saluran Irigasi Bayongbong, Kec. Ciruas, Kota Serang, Banten - Setiawan, Kharisma Feri; Tanjung, Kairul; Fadhila, Muhammad Vicky; Ratunisa, Aura; Ariyansah, Ariyansah; Afif, Muhammad Irfan; Radityani, Fitri Afina (MAIYAH, 2024)
Irrigation canals as a vital role in supporting agriculture by ensuring optimal water distribution for crops. However, apart from being a water distribution route for agriculture, irrigation canals also have the potential to be a habitat for various fish species. Therefore, this research was conducted to assess fish biodiversity in the Bayongbong irrigation canal in Ciruas District, Serang Regency, Banten. The research was conducted in February 2024 using fishing equipment and worm bait to catch fish. Fish identification was carried out by observation based on fish morphology using a freshwater fish species identification book. The research results showed that three types of fish were caught in the Bayongbong irrigation canal, namely Rasbora argyrotaenia, Anabas testudineus, and Parachela oxygastroides. Even though the conservation status of these three fish species is still relatively low according to the IUCN Red List, there is a decline in populations of wader rays and betok fish due to unsuitable environmental conditions. Environmentally unsustainable fishing practices, as well as damage or loss of freshwater habitats pose threats to the sustainability of fish populations. To overcome this conditions, the author suggests creating a more effective management strategy, including cultivating fish for consumption and ornamental purposes to maintain the viability of fish resources in the region.